Southern enlargement of the European Union and capital account liberalization: Lessons for Central and Eastern Europe - Claudia M. Buch; Ralph P. Heinrich; Daniel Piazolo (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
The integration of the central and eastern European countries into the international capital markets has been and will be determined by the process of European Union (EU) integration. Our analysis shows that southern and eastern European countries already appear to be surprisingly similar regarding FDI flows from EU members. The central and eastern European countries, however, are likely to attract increased portfolio flows in the years to come. We argue that membership alone in a regional arrangement like the EU is neither sufficient for sustained capital inflows nor is it the guarantee for increased investment activities. Rather, domestic economic policy has to change in accordance: Liberalization matters, not only membership.
Keywords: F15; F21; F32; F43; 330; Capital Account Liberalization; European Union Enlargement; Capital Flows; Eastern Europe; Economic Growth; EU-Erweiterung; Kapitalmarktliberalisierung; Direktinvestition; Kapitalimport; Entwicklungskonvergenz; Griechenland; Portugal; Spanien; Südeuropa